Wujud Akulturasi Arsitektur Rumah Tinggal Etnis Arab di Kampung Al-Munawar 13 Ulu Palembang - Anjuma Perkasa Jaya; A. Ardiansyah; Dessa Andriyali Armarieno (Universitas Sebelas Maret Surakarta, 2024)
The ability of the Arab ethnic group to mingle with the indigenous community and the rulers of Palembang City led to cultural acculturation, including in architecture. The aim of this research is to identify the forms of architectural acculturation that occur in Arab ethnic houses in the village of Al-Munawar 13 Ulu Palembang and to find the architectural typology of these houses. The research method used in this research is a descriptive qualitative method. The results of the research found that the architectural acculturation that occurred in Arab ethnic house buildings in Al-Munawar village did not lead to new architectural styles but one style became dominant over the other styles. Rumah Tinggi and Rumah Darat where the Palembang architectural style has become more dominant than the Arabic architectural style, while in the Rumah Batu, Land Twin House, Glass House, and Sea Twin House the colonial architectural style has become very dominant over the Palembang and Arab architectural styles.